Animal feed: the way forward - Loh, Teck Chwen (Universiti Putra Malaysia Press, 2017)
The poultry and livestock industry is a globalised industry and poultry is one of the fastest growing sectors in Malaysia. Malaysians are one of the highest poultry meat consuming populations in the world with per-capita consumption of about 40 kg/person/year and the overall consumption is expected to increase over the years. Even though our self-sufficiency level (SSL) is high for poultry and swine production, there is a need to meet the increasing meat demands, not just in the local but also in the international market. Animal feedstuffs and feed additives, which are largely imported, are getting costlier by the day resulting in a higher cost of production which is a major setback for our local animal production industry. This has prompted animal scientists to seek alternatives to formulate a more cost effective feed that is able to meet the minimum nutrient requirements of animals without compromising the quality of the output. Focus has been given to postbiotic metabolites produced from lactic acid bacteria (LAB) and other additives such as prebiotic, probiotic, organic acids and phytogenic compounds due to various factors such as food safety concerns. Locally available agricultural waste which is produced abundantly by agriculture sector, such as palm kernel cake, is important in our research, as feedstuff for animal feeding. The mechanisms of postbiotic metabolite actions and their importance are discussed herein. Today’s lecture covers the need for constant research in this area and to explore newer approaches for animal production. On the application aspect, this lecture will provide substantial information on future prospects of environmental friendly feed additives and precision in feed formulation.